1995
DOI: 10.1079/pns19950014
|View full text |Cite
|
Sign up to set email alerts
|

Understanding fat preference and consumption: applications of behavioural sciences to a nutritional problem

Abstract: Because of the associations between fat intakes and the development of several major chronic diseases, governmental and health authorities in Western nations have voiced consistent recommendations for reductions in fat consumption over the past 35 years (Cannon, 1992). In these countries, fat consumption has been arguably the foremost public health nutrition issue over most of this period; yet, in contrast to the massive accumulation of human and animal studies related to the potential physiological and pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

1996
1996
2001
2001

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 56 publications
0
10
0
2
Order By: Relevance
“…This may simply reflect the highly palatable properties of fat to this healthy population. 50 However, macronutrient preference within patient groups showed the BC group to have a preference for the high fat, high CHO food. This finding was surprising, as the dietary intake of fat is often prescriptively reduced in this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…This may simply reflect the highly palatable properties of fat to this healthy population. 50 However, macronutrient preference within patient groups showed the BC group to have a preference for the high fat, high CHO food. This finding was surprising, as the dietary intake of fat is often prescriptively reduced in this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…These examples have little to do with the general population at large, rather they illustrate the extremes to which FB can adapt to intense physiological demands imposed by very high levels of physical activity (Saris, 1989) or severe malnutrition. Despite these recorded extremes of energy and nutrient intake Mela (1995) points out that Western populations who have economic and market access to diets of very similar ranges of composition appear to consume, on average, around 37 ± 42% of their food energy as fat. As the Western diet becomes increasingly imposed on, or adopted by, a number of less developed nations, obesity and non insulin dependent diabetes mellitus approach epidemic proportions (WHO, 1990).…”
Section: Energy and Nutrient Relationships Within Foods Ingested By Hmentioning
confidence: 99%
“…These recommendations have led to a near fat-phobia amongst some Western consumers. Ironically, it has been recognised for more than 50 y that it is dif®cult to change habitual forms of behaviour (Gorder et al, 1986;Buzzard et al, 1990;Kristal et al, 1992;Mela 1995;Brownell & Cohen 1995). Therefore it is not surprising that in practice it appears dif®cult to entice the population to spontaneously reduce fat intake and increase levels of physical activity.…”
mentioning
confidence: 99%
“…Time is another critical element that must be considered in evaluating the success of¯avor conditioning trials. Preferences for sensory qualities are acquired or enhanced via a temporal link with reinforcing physiological or psychological outcomes, which takes time to develop (Mela, 1995). Food-deprived rats will initially consume comparable amounts of nutritive (corn oil-based) and nonnutritive (mineral oil) emulsions.…”
Section: Discussionmentioning
confidence: 99%
“…While it is generally known that these foods are typically preferred for their positive hedonic properties (Mela, 1995), the potential physiological (metabolic) factors underlying fat consumption and preference are less well understood. Studies in both humans and laboratory animals have shown that subjects can learn to unconsciously associate the sensory attributes of certain foods with their post-ingestive effects through repeated consumption.…”
Section: Introductionmentioning
confidence: 99%